Law in Literature: Juveniles’ Minds and Perspectives - Bashar, Zahirul; Khan, Shah Ahsan Ahmed (Kathmandu School of Law Review, 2022)
Expressions of language verbalize the inner thinking of authors, leading to the connection of law and literature. In this paper, the authors try to visualize the relationship between the two. Along with the western relation between law and literature, the authors try to capture and articulate this intricate relationship from Bangla Literature as well. This article outlines the complex yet interdisciplinary nexus between the law and the literature which has been developed over hundreds of years and tries to envisage the nexus between the two. Accordingly, it also seeks to understand how the two influence each other.